Pengembangan Virtual Laboratory Biology Pada Praktikum Pengamatan Protista Kelas X SMA - Alya Febrina Nasution; Kartika Manalu; Miza Nina Adlini (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This research aims to develop learning media in the form of a virtual laboratory for practicum observing protists and to find out how to develop procedures, their practicality and their effectiveness. This research is a Research and Development (R&D) research with a 4 D research design, namely: define, design, develop, and disseminate,/1 however this research was only carried out to the develop stage due to researcher limitations. The subjects in the research were 30 class X students of SMA Negeri 1 Perbaungan. The research instruments used are validation sheets from media experts and material experts to measure the validity of the virtual laboratory, response sheets from field practitioners (Teachers) and students to measure the practicality of the virtual Laboratory. The research results show that the virtual laboratory has an appropriate category based on the percentage of validity by media expert validators of 80.33%, material expert validators of 98.66%. The virtual laboratory was declared very feasible based on the percentage obtained from student responses in phase I product trials of 92.71%, phase II product trials of 86.58%, and the percentage based on teacher responses was 100%. Recommendations for future researchers and teachers to develop a three-dimensional virtual laboratory to provide a more real experience for students when simulating a practicum.